AR-AR AND U-PB AGES OF MARBLE-HOSTED RUBY DEPOSITS FROM CENTRAL AND SOUTHEAST ASIA - Garnier V.; Giuliani G.; Ohnenstetter D.; Maluski H.; Schwarz D. (My University, 2006)
To date the formation of ruby deposits and link it to the regional metamorphism associated with Tertiary Himalayan orogenesis, 40Ar-39Ar stepwise heating experiments were performed on single grains of phlogopite syngenetic with ruby, and zircon inclusions in ruby and spinel were dated with the U-Pb method by ion-probe. The Ar-Ar ages of phlogopites associated with ruby are Oligocene (24.7 ± 0.3 Ma) at Jegdalek in Afghanistan; Miocene at Mogok in Myanmar (18.7 ± 0.2 to 17.1 ± 0.2 Ma), at Hunza in Pakistan (10.8 ± 0.3 to 5.4 ± 0.3 Ma), and Chumar in Nepal (5.6 ± 0.4 Ma); and Pliocene (4.6 ± 0.1 Ma) at Ruyil in Nepal. In Vietnam, a zircon included in a ruby from the Quy Chau deposit yielded a 238U-206Pb age of 53.8 ± 4.6 Ma, whereas in the Red River shear zone, ruby formed at around 40-36 Ma during ductile deformation under peak metamorphic conditions. The ages obtained in this study are in agreement with those previously published for the ruby-bearing metamorphic belts and document extensional tectonics that were active from Afghanistan to Vietnam between the Oligocene and the Pliocene. Ruby-bearing marbles define a high-quality gem belt linked to the high-temperature metamorphism of the Himalayan fold belt that developed during the Tertiary collision of the Indian plate with Asia. © 2006 NRC Canada.
Keywords: Pliocene; Miocene; Oligocene; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен; Cenozoic::Paleogene::Oligocene; Кайнозой::Палеоген::Олигоцен